Evaluasi Profil Sensori Sediaan Pemanis Komersial Menggunakan Metode Check-All-That-Apply (CATA) - Dede Robiatul Adawiyah; Kariska Iswari Yasa (Department of Food Science and Technology (ITP), Faculty of Agricultural Technology, Bogor Agricultural University (IPB) in collaboration with the Indonesian Food and Beverage Association (GAPMMI), the National Agency of Drug and Food Control, and th, 2017)
Table-top sweetener is sweeteners in the form of granule, powder, tablet or liquid ready to be consumed as final product are packed in disposable packaging. CATA is a simple and valid tools for gathering information about food products based on consumer perception. There were two steps in CATA method: a panelist selection part and a sensory testing part. The objective of this study were to (1) profiled sensory characteristics of ideal sweetener and commercial table-top sweeteners by non-diabetic and diabetic panelists, (2) identified the panelist preferences mapping for commercial table-top sweeteners, and (3) identified the potential sensory attributes in table-top sweetener development. CATA analysis results with XLSTAT 2016 software indicates that perception ideal sweeteners by non-diabetic panelists have a sensory profile that sweet, sweet aftertaste, body and cooling. A, B, and D come closest to the ideal sweetener. Meanwhile perception ideal sweetener by diabetic panelists have a sensory profile that sweet and body. D come closest to ideal sweetener. D is the most favored product by non-diabetic and diabetic panelists, because D get a preference value above the average from all panelists. There is no correlation between the sensory attributes and panelist preference that significant at 5% sign level, it means that there is no table-top sweetener sensory attributes that control panelist preference significantly. In product development, table-top sweeteners for non-diabetic consumer must not have a bitter aftertaste and nice to have a sweet aftertaste. Meanwhile table top sweeteners for diabetic consumer must have a body attribute but not significant at 5% test level.